Non-linearity between price inflation and labor costs: The case of Central European countries - Alena Pavlova (Charles University in Prague, Institute of Economic Studies (IES), 2022)
This article explores the relationship between labor costs and price inflation under two conditions. Firstly, with linear assumption and classical techniques. Secondly, without assuming linearity, by a novel non-parametric machine learning method, namely gradient boosting. With quarterly data from 1996 to 2022 for V4 countries, we find linear and non-linear dependency between labor cost and price inflation. However, the magnitude of the connection is country-specific and changes over time. Our findings indicate that a significant linear relationship between considered variables does not lead to the higher predictability power of labor cost in a non- parametric model, which predicts inflation. Even opposed, the Czech Republic, the country with the highest correlation between unit labor cost(ULC) and deflator, shows better prediction in a case when the ULC is not in the set of independent variables. This fact highlights the importance of non-linearity for the inflation model.
Keywords: E24; E31; E37; 330; inflation; labor cost; non-linear model; V4 countries